On the Timing Ability of Mutual Fund Managers - Bollen, Nicolas P. B.; Busse, Jeffrey A. (Journal of Finance, 2001)
Existing studies of mutual fund market timing analyze monthly returns and find little evidence of timing ability. We show that daily tests are more powerful and that mutual funds exhibit significant timing ability more often in daily tests than in monthly tests. We construct a set of synthetic fund returns in order to control for spurious results. The daily timing coefficients of the majority of funds are significantly different from their synthetic counterparts. These results suggest that mutual funds may possess more timing ability than previously documented.